3
$\begingroup$

Let $0\leq x<1$ and $s_n$ be a sequence of partial sums of the series $\sum_{n=0}^{\infty}a_n$. It is called that the series $\sum_{n=0}^{\infty}a_n$ is $(A)$ or Abel summable to $s$ if $$\lim_{x\to1^-}(1-x)\sum_{n=0}^{\infty}s_nx^n=s,$$ and the series $\sum_{n=0}^{\infty}a_n$ is called $(L)$ summable to $s$ if $$\lim_{x\to1^-}\frac{-1}{\log(1-x)}\sum_{n=0}^{\infty}\frac{s_n}{n+1}x^{n+1}=s.$$

I need help to prove $(A)$ summability of the series $\sum_{n=0}^{\infty}a_n$ to $s$ implies $(L)$ summability of the series $\sum_{n=0}^{\infty}a_n$ to $s$. That is $(L)$ summability includes $(A)$ summability.

$\endgroup$
  • $\begingroup$ Your definition of Abel summability seems wrong. As written, every summable sequence $(s_n)$ would be Abel summable to $0$. $\endgroup$ – Daniel Fischer Feb 24 '15 at 10:54
  • $\begingroup$ The definition is from the book of Jacob Korevaar: Tauberian Theory from Section 1: Equation (1.2). $\endgroup$ – Raio Feb 24 '15 at 11:06
  • $\begingroup$ I can't see Section 1, but from examples 2.2 and 2.3, it seems that the sequence $(a_n)$ is Abel summable to $s$ if $$\lim_{x\to 1^-} (1-x)\sum_{n=0}^\infty s_n x^n = s,$$ where the $(s_n)$ are the partial sums, $$s_n = \sum_{k=0}^n a_k.$$ That looks more sensible. $\endgroup$ – Daniel Fischer Feb 24 '15 at 11:14
  • $\begingroup$ i edited the question. $\endgroup$ – Raio Feb 24 '15 at 18:32
3
+50
$\begingroup$

$$ \begin{matrix} \text{Let} & F(x) = \sum\limits_{n=0}^\infty \frac{s_n}{n+1} x^{n+1} &\text{so}& F'(x) = \sum\limits_{n=0}^\infty s_n x^n \\ \text{and} & G(x) = -\log(1-x) &\text{so}& G'(x)=\frac1{1-x} \\ \text{then} & -\dfrac1{\log (1-x)}\sum\limits_{n=0}^\infty \dfrac{s_n}{n+1}x^n=\dfrac{F(x)}{G(x)} &\text{and}& (1-x)\sum\limits_{n=0}^\infty s_nx^n=\dfrac{F'(x)}{G'(x)}. \\ \end{matrix} $$

We want to prove that $\lim\limits_{x\to1-0} \dfrac{F'(x)}{G'(x)}=s$ implies $\lim\limits_{x\to1-0} \dfrac{F(x)}{G(x)}=s$.

As $\lim\limits_{x\to1-0}G(x)=\infty$, this is true by L'Hospital's rule.

(Most textbooks state L'Hospital's rule for limits of the forms $\frac00$ and $\frac{\pm\infty}{\pm\infty}$, but the case $\lim |G|=\infty$ no assumption is required on $\lim F$.)

$\endgroup$
  • 2
    $\begingroup$ I cant find any example for the converse case is not true. Namely, there exists a sequence which is summable (L) but not summable (A). Do you see any example for this case? $\endgroup$ – Raio Feb 27 '15 at 18:16
  • 3
    $\begingroup$ You can start with finding a suitable $F(x)$. For example $F(x)=\sin\frac1{1-x}$ is bounded so $\lim_{x\to1-0}\frac{F(x)}{-\ln(1-x)}=0$ but $F$ oscillates too rapidly: $(1-x)F'(x)=\frac{\cos\frac1{1-x}}{1-x}$ which has no limit. Now you can take the Taylor coefficients of $F'$ at $0$. $\endgroup$ – user141614 Feb 28 '15 at 7:22

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.